2013
DOI: 10.5050/ksnve.2013.23.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Condition Monitoring of Low Speed Slewing Bearings Based on Ensemble Empirical Mode Decomposition Method

Abstract: Vibration condition monitoring of low-speed rotational slewing bearings is essential ever since it became necessary for a proper maintenance schedule that replaces the slewing bearings installed in massive machinery in the steel industry, among other applications. So far, acoustic emission(AE) is still the primary technique used for dealing with low-speed bearing cases. Few studies employed vibration analysis because the signal generated as a result of the impact between the rolling element and the natural def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Ž vokelj et al (2010) showed that, based on a principal component analysis (PCA) statistical indicator and by the use of the ensemble empirical mode decomposition (EEMD) of vibration and acoustic emission (AE) signals of a machine rotating at 8 rpm, a faulty bearing condition could be identified. Caesarendra et al (2013) then proposed to extract slewing bearing (rotating at 15 rpm) defect information in vibration signals via EEMD, and in Caesarendra et al (2014) the authors proposed to extract the slewing bearing defect information (at 1 rpm) from the vibration signal by reducing the number of samples using 'piecewise aggregate approximation' (PAA), elliptic shape identification (ellipse least-square fitting) of the neighborhood correlation plot and finally by the use of circular statistical indicators. According to the authors, these indicators gave a better estimation of the bearing condition than the ones resulting from Empirical Mode Decomposition (EMD) and wavelet transform.…”
Section: Low Speed Bearings Fault Diagnosismentioning
confidence: 99%
“…Ž vokelj et al (2010) showed that, based on a principal component analysis (PCA) statistical indicator and by the use of the ensemble empirical mode decomposition (EEMD) of vibration and acoustic emission (AE) signals of a machine rotating at 8 rpm, a faulty bearing condition could be identified. Caesarendra et al (2013) then proposed to extract slewing bearing (rotating at 15 rpm) defect information in vibration signals via EEMD, and in Caesarendra et al (2014) the authors proposed to extract the slewing bearing defect information (at 1 rpm) from the vibration signal by reducing the number of samples using 'piecewise aggregate approximation' (PAA), elliptic shape identification (ellipse least-square fitting) of the neighborhood correlation plot and finally by the use of circular statistical indicators. According to the authors, these indicators gave a better estimation of the bearing condition than the ones resulting from Empirical Mode Decomposition (EMD) and wavelet transform.…”
Section: Low Speed Bearings Fault Diagnosismentioning
confidence: 99%
“…These results provide the contribution of EMD and EEMD application in real bearing case, where the faults are developed naturally whereas the most discussed literature were used EMD and EEMD for artificial bearing fault data. Earlier study which reported the application of EMD and EEMD for slewing bearing naturally damage data is presented in [19]. The rotational speed of slewing bearing was 15 rpm.…”
Section: Discussionmentioning
confidence: 99%